Innovative Strategies for Customer Satisfaction in Service Quality: A Case Study of Indonesian Islamic Banks in Pekanbaru - Endrianto Ustha; Ratna Nurani (Lembaga Riset dan Inovasi Al-Matani, 2025)
ABSTRACT This study aims to analyze the level of customer satisfaction with service quality and the strategies to improve customer satisfaction at Bank Syariah Indonesia KCP Arifin Ahmad, Pekanbaru. Data collection techniques included primary data obtained from questionnaires and interviews. The sampling method used was Simple Random Sampling, with respondents being customers of Bank Syariah Indonesia KCP Arifin Ahmad. Data analysis was performed using the Customer Satisfaction Index (CSI) method through Microsoft Excel and SWOT analysis. The indicators used to measure the level of customer satisfaction with service quality in Islamic banking consist of six dimensions: Reliability, Responsiveness, Assurance, Empathy, Tangibles, and Compliance with Islamic Law. The results of the study, using CSI, showed a score of 66.04%, which falls within the range of 66.00-80.00, indicating that customers are satisfied with the service quality provided by Bank Syariah KCP Arifin Ahmad. The results of the SWOT analysis suggest that Islamic banks need to implement several strategies to increase customer satisfaction. These strategies include setting competitive pricing, maintaining and expanding cooperation networks with existing partners, continuing to enhance customer convenience by increasing ATM facilities, improving service quality by offering additional services, and optimizing the system by enhancing IT infrastructure or applications.